2017
DOI: 10.1177/0194599817731740
|View full text |Cite
|
Sign up to set email alerts
|

Single‐Blinded Prospective Implementation of a Preoperative Imaging Checklist for Endoscopic Sinus Surgery

Abstract: Objective To determine if the introduction of a systematic preoperative sinus computed tomography (CT) checklist improves identification of critical anatomic variations in sinus anatomy among patients undergoing endoscopic sinus surgery. Study Design Single-blinded prospective cohort study. Setting Tertiary care hospital. Subjects and Methods Otolaryngology residents were asked to identify critical surgical sinus anatomy on preoperative CT scans before and after introduction of a systematic approach to reviewi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(29 citation statements)
references
References 8 publications
(19 reference statements)
2
23
0
4
Order By: Relevance
“…A structured approach to CT scans of the paranasal sinuses using the CLOSE criteria can further improve identi cation of critical anatomical variants signi cantly. These positive results have previously been shown in otolaryngology residents [22]. Error et al showed a signi cant improvement in identi cation of critical anatomical structures in sinus CT scans after the implementation of the CLOSE criteria in 9 junior and 9 senior residents.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…A structured approach to CT scans of the paranasal sinuses using the CLOSE criteria can further improve identi cation of critical anatomical variants signi cantly. These positive results have previously been shown in otolaryngology residents [22]. Error et al showed a signi cant improvement in identi cation of critical anatomical structures in sinus CT scans after the implementation of the CLOSE criteria in 9 junior and 9 senior residents.…”
Section: Resultssupporting
confidence: 61%
“…Error et al also analyzed the individual CLOSE items and found a signi cant improvement postimplementation for all items except lamina papyracea [22]. We found an improvement for all items in residents and all items in students except for lamina papyracea.…”
Section: Resultssupporting
confidence: 56%
See 1 more Smart Citation
“…Several checklists have also been developed for the preoperative evaluation of CT scans prior to sinus surgery. Some of them are very detailed, thus extensive, and some include general safety aspects [70][71][72][73][74][75][76]. Some of these checklists have been validated.…”
Section: Surgical and Radiological Checklistsmentioning
confidence: 99%
“…There is great diversity in sinonasal anatomy and sinonasal landmarks (10,11) , so it is necessary to have a detailed study of radiological images in order to assess each patient individually (12) . Checklists based on radiological images have been used to improve ESS and reduce avoidable surgical mistakes, through the systematization of the necessary steps during surgery (13)(14)(15) .…”
Section: Introductionmentioning
confidence: 99%